2023
DOI: 10.1126/sciimmunol.add5204
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive reprogramming of neutrophils by lung mesenchymal cells promotes breast cancer metastasis

Abstract: Neutrophils, the most abundant innate immune cells, function as crucial regulators of the adaptive immune system in diverse pathological conditions, including metastatic cancer. However, it remains largely unknown whether their immunomodulatory functions are intrinsic or acquired within the pathological tissue environment. Here, using mouse models of metastatic breast cancer in the lungs, we show that, although neutrophils isolated from bone marrow (BM) or blood are minimally immunosuppressive, lung-infiltrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 94 publications
(127 reference statements)
4
16
0
Order By: Relevance
“…The involvement of these cells should be considered in future research, as their metabolic contributions may result in tissue-specific immunosuppression. 10 Importantly, many therapeutic nanomedicines reach their intracellular targets via endocytosis. 182 Therefore, other than tumor cells, tumor targeting nanoparticles could be most easily internalized by antigen-presenting cells with phagocytic functions, such as DCs and macrophages.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…The involvement of these cells should be considered in future research, as their metabolic contributions may result in tissue-specific immunosuppression. 10 Importantly, many therapeutic nanomedicines reach their intracellular targets via endocytosis. 182 Therefore, other than tumor cells, tumor targeting nanoparticles could be most easily internalized by antigen-presenting cells with phagocytic functions, such as DCs and macrophages.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Lipid metabolism of both tumor cells and neutrophils in the TME can profoundly influence TAN recruitment and function, and tumor-derived oxysterols contribute to neutrophil recruitment . Recent research demonstrated that in the lung microenvironment, lung mesenchymal cells could significantly enhance the expression of immunosuppressive genes via PGE2, which explained the tissue-dependent immunosuppression of neutrophils . Importantly, in patients, ER stress-related genes can be induced in immunosuppressive neutrophils, altering lipid metabolism, and increasing the expression of ROS, arginase 1 (ARG1), and PGE2, leading to immunosuppression. ,, Thus, tumor cell lipid metabolism can promote neutrophil immunosuppressive function, and neutrophils can, in turn, contribute to the accumulation of toxic metabolites as well as nutrient depletion.…”
Section: Tumor Cell Metabolism and Immunosuppressionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the eicosanoid prostaglandin E 2 (PGE 2 ) partially mediated the suppression of CD4 + T cells by neutrophils from individuals with sepsis, as an antagonist of the cognate receptor restored the expression of the lymphocyte-activation markers CD69 and PD-1, but not the proliferation of CD4 + T cells 2 . This finding is exciting and deserves further testing, also considering the multifaceted immunological functions of PGE 2 in tumor-associated neutrophils 8,9 . However, many other suppressive mechanisms are at play, such as the release of immune-modulating cytokines, reactive oxygen species (ROS), granules or neutrophil extracellular traps (NETs) 7 .…”
mentioning
confidence: 93%